Intraparenchymal endodermal cyst with spontaneous intracystic hemorrhage in the temporal lobe of an adult. Issue 46 (November 2016) - Bao, Xin-Jie; Li, Xue-Yuan; Wang, Qi-Pu; Ren, Xin-Yu; Liang, Zhi-Yong; Ma, Wen-Bin; Wang, Ren-Zhi; Wei, Jun-Ji
Abstract: Background: Endodermal cysts (EC) are rare but well-known congenial lesions of the central nervous system mainly located in the spinal subdural space. Intracranial ECs are rare and commonly encountered in the posterior cranial fossa as extra-axial lesions; an intraparenchymal location is exceedingly rare. A complete removal is the best surgical strategy and any residue can cause recurrence. It is necessary to exclude EC in patients with intracranial cystic lesions. We present a case of intraparenchymal EC with spontaneous intracystic hemorrhage in the temporal lobe of an adult. Methods: A 43-year-old man presented with headache and memory deterioration. Brain computed tomography and magnetic resonance imaging showed a slightly enhanced temporal lobe cystic lesion, which was homogenously hyperintense on T1-and T2-weighted images. There was a suspicion of brain abscess at admission. The lesion was totally removed with a left subtemporal craniotomy. Histological examination revealed an EC with intracystic hemorrhage. Results: The preoperative symptoms were relieved after surgery and 3-month follow-up magnetic resonance imaging found no cystic signs. Conclusion: This case suggests that EC should be considered in the differential diagnosis of intracranial cystic lesions and a complete removal is the best strategy of choice.